Morphometric and Ultrastructure studies of Primordial Follicles and Expression of Estrogen-dependent Genes in the Ovaries of Domestic Cats. Issue 1 (March 2016) - Ariel, Odenheimer; Yao, Shaomian; Kearney, Michael T.; Joudrey, Scott D.; Al-Bagdadi, Fakhri
Abstract: The aim of this study was to compare and estimate the population of the primordial follicle morphometrically and ultrastructurally in the left and right side ovaries of 10 ovariohysterectomied healthy domestic shorthair cats. The ovaries were processed for light microscopy, electron microscopy, and estrogen-dependent gene expression for assessments. A total of 15, 092 primordial follicles with and without a nucleus were examined and counted. A total of 6842 primordial follicles with a nucleus were examined and counted. The light-microscopy numerical data were collected from two histological sections per ovary for a total of 20 sections from the left ovary and 20 sections from the right ovary. The average surface area of the histological sections was 645.99 mm 2 . The number of tertiary follicles was found to be higher in the left ovaries than in the right ovaries. The primordial follicles are under the tunica albuginea at various levels. Some are crowded or scattered in one or two rows, although at times, there were areas without any primordial follicles. The primordial follicles varied in size, and were surrounded by 4–10 squamous granulosa cells. Some primordial follicles shared their ooplasm with one or two neighboring primordial follicles, forming a giant primordial follicle with two or three nuclei. The ultrastructure of the primordial follicles showed rounded nuclei with distinct nucleoli, rounded and elongated mitochondria, and a considerably thick basement membrane under the granulosa cells. The squamous granulosa cells showed well-developed microvilli intermingled with the microvilli of the oocyte oolemma. Elongated mitochondria, coated pits, multicytoplasmic vesicles, ribosomes, and Golgi apparatuses were obvious in the oocyte ooplasm. Large vesicles contain small multivesicles and some scattered lipid globules in the ooplasm. There were estrogen-dependent gene-expression differences between the right and left ovaries. Further gene research is in the plan, using a larger pool of cats, with a focus on age differences.